BULLYING AND ITS FOUR FUNCTIONS: A STUDY OF YOUNG OFFENDERS IN JUVENILE JUSTICE INSTITUTIONS - Hassan, Nazirah (International Journal of Psychosocial Rehabilitation, 2020)
Bullying in secure settings has been identified as an ongoing and serious issue in a range of different countries. This study investigates the prevalence of bullying and victimisation in juvenile justice institutions in Malaysia, where research on this phenomenon has been particularly limited. It further explores the circumstances that underpin bullying behavior in the institutions. The study comprised a survey completed by 289 male and female young people, aged 12 to 21 years old, in 8 juvenile justice institutions, using the scale version of Direct and Indirect Prisoner behaviour Checklist (DIPC-SCALEDr). In addition, interviews were carried out with 16 young people and 8 staff members, comprising both male and female participants. The survey findings showed that 95 per cent of young people reported at least one behaviour indicative of bullying others, and 99 per cent reported experience of being victimized at least once in a month. The DIPC-SCALEDr scored significantly higher on physical, verbal and psychological forms of bullying and victimization. Nonetheless, young people reported higher score on sexual form of victimization. In the interviews, young people identified four circumstances underpinning bullying behaviour in the institutions, including ‘protecting oneself from threatening events’, ‘exerting control over others’, ‘access to goods’ and ‘building alliances.’ Most bullies hold more positive beliefs about the use of aggression and perceived bullying as a powerful tool which serves survival and protection for them. These findings may have implications for bullying perpetration and victimization prevention in juvenile justice institutions.